The Factors Associated with the Utilization of Voluntary Counseling and Testing Services in Antenatal Care - Astriana Adistie, Hana (Jurnal Indonesia Sosial Sains, 2026)
Background: The VCT (Voluntary Counseling and Testing) examination at Community Health Center Gate Raya in 2021 only reached 46% and in 2022 approximately 76% of the 100% target. Objective: To identify the factors associated with the utilization of VCT services during antenatal care in the working area of UPT Puskesmas Gebang Raya. Methods: This study employed a descriptive quantitative method with a cross-sectional approach. The sampling technique used purposive sampling with a sample size of 101 pregnant women. The data was collected using an online Zoho form platform with a questionnaire assessing knowledge, readiness, and family support in relation to the utilization of VCT services, directly connected to the researchers e-mail. The chi-square test with a significance level of α= < 0.05 was conducted in July 2023 at UPT Puskesmas Gebang Raya. Results: Out of 101 respondents, 46 (45.5%) had low knowledge and 55 (54.5%) had high knowledge. Respondents with a negative attitude totaled 61 (60.4%), while those with a positive attitude totaled 40 (39.6%). The study results indicate a significant relationship between knowledge and the utilization of VCT services with a p-value of 0.000<0.05. The relationship between attitude and the utilization of VCT services showed a p-value of 0.003<0.005. Conclusion: There is a significant relationship between high knowledge, resulting in a positive attitude, and good behavior in using VCT services. Recommendations: Effective communication media are needed for counseling to enhance the effectiveness of VCT services, particularly increasing the knowledge level of pregnant women regarding VCT services.